Polyvagal perspective on ethnic distance and well-being in Bosnia-Herzegovina - Kuhar, Metka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
In this study, the responses of 182 Bosniaks were analysed to examine the interplay between previous adversity (past challenging or traumatic experiences a person has faced), mental well-being, and ethnic distance in Bosnia and Herzegovina through the lens of polyvagal theory, which emphasises the role of physiological reactivity and body awareness. The results show that there is no direct association between past adversity and well-being or ethnic distance. However, previous adversity is a significant predictor of autonomic reactivity and body awareness, which serve as mediators of well-being and ethnic distance. These findings point to the potential benefits of trauma-informed interventions to improve social cohesion in post-conflict settings.
Keywords: adversity; autonomic reactivity; avtonomna reaktivnost; body awareness; Bosna in Hercegovina; Bosnia-Herzegovina; duševno blagostanje; ethnic distance; etnična distanca; mental well-being; polivagalna teorija; polyvagal theory; stiska; telesno zavedanje